Extravasating Neutrophils Open Vascular Barrier and Improve Liposomes Delivery to Tumors - Naumenko, Victor A; Vlasova, Kseniya Yu; Garanina, Anastasiia S; Melnikov, Pavel A; Potashnikova, Daria M; Vishnevskiy, Daniil A; Vodopyanov, Stepan S; Chekhonin, Vladimir P; Abakumov, Maxim A; Majouga, Alexander G (ACS nano, 2019)
Liposomes are the most extensively used nanocarriers in cancer therapy. Despite the advantages these vehicles provide over free drugs, there are still limitations with regards to the efficiency of liposomes delivery to tumors and off-target accumulation. A better understanding of nanodrugs extravasation mechanisms in different tumor types and normal vessels is needed to improve their antitumor activity. We used intravital microscopy to track for fluorescent liposomes behavior in xenograft tumor models (murine breast cancer 4T1 and melanoma B16, human prostate cancer 22Rv1) and normal skin and identified two distinct extravasation patterns. Microleakage, a local perivascular nanoparticle deposition, was found both in malignant and healthy tissues. This type of liposomes leakage does not provide access to tumor cells and is presumably responsible for drug deposition in normal tissues. In contrast, macroleakage penetrated deep into tissues and localized predominantly on the tumor–host interface. Although neutrophils did not uptake liposomes, their extravasation appeared to initiate both micro- and macroleakages. Based on neutrophils and liposomes extravasation dynamics, we hypothesized that microleakage and macroleakage are subsequent steps of the extravasation process corresponding to liposomes transport through endothelial and subendothelial barriers. Of note, extravasation spots were detected more often in the proximity of neutrophils, and across studied tumor types, neutrophils counts correlated with leakage frequencies. Reduced liposomes accumulation in 4T1 tumors upon Ly6G depletion further corroborated neutrophils role in nanoparticles delivery. Elucidating liposomes extravasation routes has a potential to help improve existing strategies and develop effective nanodrugs for cancer therapy.